MENAVIGASI NILAI DAN GAGASAN MODERASI BERAGAMA DALAM MASYARAKAT KONTEMPORER - Rusiadi Rusiadi (Adisam Publisher, 2025)
Exploring the concept of religious moderation and its relevance in contemporary society, aiming to distinguish it from fundamentalism, extremism, and liberalism. I provide a conceptual framework for understanding religious moderation, examining its etymology, historical context, and interdisciplinary interpretations. The core values of moderation—tolerance, empathy, dialogue, and inclusivity—are analysed alongside the principles of contextual interpretation of religious texts and the role of ethics and social justice. Through concrete examples from Christianity, Islam, Judaism, and other religious traditions, I highlight how these principles are manifested in practice. Furthermore, I discuss the challenges and criticisms faced by religious moderation from conservative and secular perspectives, emphasising the delicate balance between religious belief and inclusivity in a diverse society. This comprehensive analysis aims to contribute to a deeper understanding of how religious moderation can promote peaceful coexistence and social justice in an increasingly polarised world.